Case Report: Diagnosis and treatment of giant thoracodorsal liposarcoma - Liu, Kailin; Zhao, Baoyan; Ren, Ningning; Zhao, Peng; Wang, Zhihao; Li, Xia; Li, Yuyang; Geng, Chong (Frontiers in Oncology, 2025)
RationaleLiposarcoma is a prevalent malignant tumor of soft tissue; however, those in the thoracic and back regions are rare, and surgery is particularly challenging due to their complex anatomical structures.Case presentationA 90-year-old man was admitted to the hospital due to a massive lump in the thoracodorsal region. Computerized tomography imaging revealed a large heterogeneous lesion with lipid density in the left axillary chest wall area, with a maximum cross-sectional area of approximately 17.4 × 14.2 cm. The histopathologic report showed a well-differentiated liposarcoma.Clinical discussionEarly detection and timely intervention of liposarcoma are critical, particularly for large liposarcomas in the thoracodorsal region because of the surrounding vital structures, such as the brachial plexus, axillary vein, and axillary artery. We found that the liposarcoma was infiltrated by M2 macrophages, with the central region exhibiting high rates of M0 macrophages and Treg cells. This immunosuppressive tumor microenvironment may provide a potential target for the development of immunotherapeutic strategies.